SYMBOLIC VIOLENCE BASED ON GENDER (DESCRIPTIVE STUDY IN YOUNG ADULT INSTAGRAM USERS IN MEDAN CITY) - Nurbani; Sabilla Tri Ananda M. Si; Nurul Sakina S. Hum (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Social media is expected to be a free area, but in reality, the social media users cannot be separated from the dominance and symbolic violence, while in social media there are users who dominate the other users. This study analyzes how symbolic violence based on gender occurs on social media. Social media users engage in symbolic violence through the text they convey as an attempt to introduce a certain understanding or interests. Using the symbolic theory of violence by Pierre Bordieu, researchers used a qualitative approach with data collection methods through in-depth interviews, documentation and secondary data on students of social media users in Medan City. University students are chosen to be informants, as they are expected to have good knowledge of gender issues.